2007
DOI: 10.1007/s00441-007-0530-3
|View full text |Cite
|
Sign up to set email alerts
|

microRNA and stem cell function

Abstract: The identification and characterization of stem cells for various tissues has led to a greater understanding of development, tissue maintenance, and cancer pathology. Stem cells possess the ability to divide throughout their life and to produce differentiated daughter cells while maintaining a population of undifferentiated cells that remain in the stem cell niche and that retain stem cell identity. Many cancers also have small populations of cells with stem cell characteristics. These cells have been called c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 136 publications
(136 reference statements)
1
100
0
2
Order By: Relevance
“…28 An important theme is the emerging role of microRNAs in the regulation of stem cell self-renewal and differentiation. 29 Ablation of Dicer leads to defects in embryonic stem (ES) cell division and proliferation, 30 causing death in mice and a complete loss of pluripotent stem cells. 31 Dicer ablated ES cells also fail to differentiate; thus microRNAs can affect stem cell behavior at the levels of both proliferation and differentiation.…”
Section: Micrornas In Neural Developmentmentioning
confidence: 99%
“…28 An important theme is the emerging role of microRNAs in the regulation of stem cell self-renewal and differentiation. 29 Ablation of Dicer leads to defects in embryonic stem (ES) cell division and proliferation, 30 causing death in mice and a complete loss of pluripotent stem cells. 31 Dicer ablated ES cells also fail to differentiate; thus microRNAs can affect stem cell behavior at the levels of both proliferation and differentiation.…”
Section: Micrornas In Neural Developmentmentioning
confidence: 99%
“…microRNAs are small, non-coding RNAs that regulate gene expression by binding to mRNA 3'UTRs, which results in mRNA degradation or translation (4)(5)(6)(7)(8). microRNA regulates embryonic development, cell proliferation, apoptosis, cell differentiation, lipid metabolism and other important cellular functions, particularly in tumor development, where its function is similar to that of oncogenes or tumor suppressor genes (9)(10)(11). When oncogenes and tumor suppressor genes are disrupted, or the activity of telomerase persists, tumorigenesis occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, these molecules could constitute a powerful therapeutic strategy for interfering with cancer initiation and progression (Garofalo and Croce, 2011). Moreover, miRNAs have been implicated in the control of self-renewal in stem cells (Hatfield and Ruohola-Baker, 2008). Georgantas et al found that miRNA-155 played a role in normal human myelopoiesis, lung differentiation, and erythropoieis, and a recent study has shown that a high level of hsamiR-155 is associated with a poor outcome in lung cancer (Georgantas et al, 2007;Wang et al, 2009b).…”
Section: Monitoring Micrornas Using a Molecularmentioning
confidence: 99%